Magnesium Oxide/Poly(l‐lactide‐co‐ε‐caprolactone) Scaffolds Loaded with Neural Morphogens Promote Spinal Cord Repair through Targeting the Calcium Influx and Neuronal Differentiation of Neural Stem Cells. Issue 15 (3rd June 2022) - Xie, Jile; Li, Jiaying; Ma, Jinjin; Li, Meimei; Wang, Xingran; Fu, Xinya; Ma, Yanxia; Yang, Huilin; Li, Bin; Saijilafu
Abstract: Because of the limited regenerative ability of the central nervous system (CNS), effective treatments for spinal cord injury (SCI) are still lacking. After SCI, neuron loss and axon regeneration failure often result in irreversible functional impairment. The calcium overload induced by the N‐methyl‐D‐aspartate receptor (NMDAR) overactivation is critical for cell death in SCI. It has been reported that the magnesium ion (Mg 2+ ) can competitively block the NMDAR and reduce the calcium influx, and that sonic hedgehog (Shh) and retinoic acid (RA) are the critical regulators of neuronal differentiation of endogenous neural stem cells (NSCs). Here, magnesium oxide (MgO)/poly (l ‐lactide‐co‐ ε ‐caprolactone) (PLCL) scaffold loaded with purmorphamine (PUR, a Shh signaling agonist) and RA is developed and its feasibility in SCI repair is tested. The results showed that the Mg 2+ released from MgO attenuated cell apoptosis by blocking the calcium influx, and the PUR/RA promoted the recruitment and neuronal differentiation of endogenous NSCs, thereby reducing the glial scar formation at the SCI lesion site. Furthermore, implantation of PUR/RA‐loaded MgO/PLCL scaffold facilitates the partial recovery of a locomotor function of SCI mouse in vivo. Together, findings from this study imply that PUR/RA‐loaded MgO/PLCL scaffold may be a promising biomaterial for the clinical treatment of SCI. Abstract : A novel PUR (purmorphamine, a Shh signaling agonist) /RA (retinoic acid)‐loaded MgO/PLCL scaffold is developed and its feasibility in spinal cord injury (SCI) repair is tested. The results showed that the Mg 2+ released from MgO reduces cell apoptosis by blocking the calcium influx, and the PUR/RA promotes the recruitment and neuronal differentiation of endogenous NSCs, thereby reducing the glial scar formation at the SCI lesion site, and significantly promotes locomotor functional recovery of SCI.